PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP HASIL BELAJAR SISWA PADA KONSEP TEKANAN ZAT CAIR DI KELAS VIII SMP PEMBANGUNAN V YAPIS TAHUN PELAJARAN 2018/2019 - Suryana, Hana; Lasmono, Paulus G. D.; Boy, Bonefasius Yanwar (Universitas Cenderawasih, 2023)
This study aims to evaluate the improvement of learning outcomes and the relationship influence of the guided inquiry model (X) on student learning outcomes on the concept of liquid pressure (Y). The type of research used is quantitative with the pre-experimental design and one group pretest-posttest design methods. The study population consisted of all students of class VIII of SMP Pembangunan V Yapis Waena, with a sample of 26 students from class VIIIA, taken through purposive sampling techniques. The instruments used include a questionnaire for the guided inquiry learning model and a learning outcome test on the concept of liquid pressure. N-gain analysis is used to measure the improvement of student learning outcomes. The relationship between variables X and Y is analyzed by simple Pearson Product Moment (PPM) correlation, while the influence between variables X and Y is analyzed by simple regression. Linearity analysis is used to examine data patterns. The results showed an increase in student learning outcomes of 0.83, which is considered high. Asymp. Sig. value. (2-tailed) = 0.016 < 0.05 indicates a significant relationship between variables X and Y, with a Pearson Correlation value = 0.466 indicating a moderate relationship. The R Square value = 0.217 indicates the effect of X on Y of 21.7%. The Sig. value = 0.016 < 0.05 indicates a significant effect between variables X and Y. The Sig. Linearity value = 0.022 < 0.05 indicates that the data follows a linear pattern with a regression equation of Y = 51.725 + 0.430 (X).